Concomitant Erythema Nodosum Leprosum and Bullous Dapsone Hypersensitivity Syndrome in Relapsed Multibacillary Leprosy: Pathophysiological Insights and Therapeutic Strategy - Nurrachmat Mulianto; Ivani; Pratiwi Prasetya Primisawitri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Multibacillary leprosy management is frequently complicated by severe immunological reactions and adverse drug events. Erythema nodosum leprosum is an immune-complex-mediated complication, while dapsone hypersensitivity syndrome is an idiosyncratic, potentially life-threatening drug reaction. The concomitant presentation of these distinct entities, especially with bullous eruptions, creates a profound diagnostic and therapeutic dilemma. Case presentation: A 42-year-old male with a history of relapsed borderline lepromatous leprosy and rheumatoid arthritis presented with exquisitely painful erythematous nodules, high-grade fever, and bullous eruptions exactly 72 hours after the re-initiation of multidrug therapy. Physical examination recorded a Visual Analog Scale pain score of 9. Expanded histopathological evaluation confirmed a dual pathology: extensive dermal neutrophilic infiltration characteristic of Erythema Nodosum Leprosum, occurring alongside pronounced subepidermal blistering and marked eosinophilic exocytosis indicative of a dapsone-induced bullous eruption. Standard multidrug therapy was immediately discontinued. A modified regimen comprising rifampicin, clarithromycin, and carefully titrated immunosuppressants (methylprednisolone and azathioprine) was initiated. Conclusion: The substitution of dapsone with clarithromycin facilitated rapid clinical resolution of both the bullous eruptions and recurrent immune reactions. This case underscores the critical need for precise temporal tracking, individualized therapeutic modifications, and comprehensive histopathological evaluation in leprosy patients demonstrating complex, overlapping hypersensitivity syndromes.